Structure and Tectonic Reconstruction of Bayah Complex Area, Banten - Jemi Saputra Ahnaf; Aton Patonah; Haryadi Permana; Ismawan Ismawan (UIR PRESS, 2018)
The research aimed to reconstruct the geological structures and tectonics of the Bayah complex area. The structures found that grouped into regional structural patterns used to determine the ages and the events that responsible to its formation. The methods used in this research include field and studio method. Field method carried out to map the outcrops and record geological structures data using geological compass, GPS, tape measurement, and geological hammer, while studio method performed to process and analyze data using software such as Win Tensor, Dips, MapInfo Professional 10.5 and CorelDraw X4. The geological structure of the Bayah has varying patterns and ages. The fracture patterns show N-S and E-W direction which is belong to Sundanese and Java Pattern formed in range of the Early Eocene to Pliocene. While the faults that have direction of SW-NE and E-W are classified into Meratus and Java Pattern. However, metamorphic rock foliations show NW-SE and N-S direction that belonging to the Pre-Tertiary Sumatra Pattern. The three faults of this research are estimated to be formed by the effect of orogenesis that occurring in different events and ages. JSA-014 fault is predicted to form due to orogeny I or orogeny II in the Early Oligocene - Middle Miocene, this fault classified as the 2nd order right lateral wrench fault. JSA-034 fault is formed by orogeny I in Early Oligocene - Middle Miocene, this fault is also classified as the 2nd order right lateral wrench fault. While JSA-080 fault has relatively young age that formed due to orogeny III in the Middle Miocene - Pliocene and belonging to the 3rd order left lateral wrench fault.